The Influence of Tax Avoidance, Harmonization of Tax Regulations and Tax Understanding on Taxpayer Compliance with Risk Preferences as a Moderating Variable in MSMEs in Makassar City - Haslindah Haslindah; Wahyuni Saleh; Ardhiatul Halima Tuasalamony; Sitti Rahma Sudirman; Muhammad Rinaldi (Jurnal Riset Perpajakan: Amnesty, 2024)
This research aims to examine the influence of tax avoidance, harmonization of tax regulations and understanding of taxation on taxpayer compliance with risk preferences as a moderation variable in MSMEs in Makassar City. The data in this research was obtained from MSMEs in Makassar City who were registered as Taxable Entrepreneurs who were willing to be respondents. This research uses primary and secondary data by conducting direct research in the field by giving questionnaires/statement sheets to 60 respondents. The data analysis technique was carried out using descriptive statistical analysis and PLS (Partial Least Square). The research results show that Tax avoidance, Harmonization of tax regulations and Tax Understanding have a positive and significant effect on the compliance of Makassar City MSME taxpayers. Tax avoidance and harmonization of tax regulations have a positive and significant effect on taxpayer compliance which is strengthened by risk preferences and understanding of taxation, which is not significant on taxpayer compliance which is moderated by risk preferences.